A INCLUSÃO DO ALUNO SURDO NO ENSINO REGULAR: POSSIBILIDADES DE PRÁTICAS PEDAGÓGICAS - ATAMANCZUK, LUCICLEIA KRIK (2023)
The general objective of this dissertation is to analyze the pedagogical possibilities, in the context of inclusive regular education, aimed at the deaf student in relation to the cultural and linguistic differences of this subject. The specific objectives are: to elaborate an overview about the daily life of the context of inclusion of deaf students in regular education in view of the analyzed case; analyze the context of inclusion of the deaf student; identify the pedagogical possibilities in student learning; and examine the pedagogical possibilities based on respect for the cultural and linguistic differences of the deaf. This is a qualitative, ethnographic research in the area of education, supported by a case study. The subject of the study is a student with profound bilateral deafness enrolled in regular education at a municipal public school in the interior of the State of Paraná. Data were collected mainly through participant and non-participant observation. Interviews and document analysis were used as a complementary way of collecting data. For the analysis, the Discursive Textual Analysis (ATD) was used. The main results identified show that there is still difficulty in effective pedagogical inclusion, due to not adequately considering the cultural and linguistic elements present in this process. Despite this, elements are observed that contribute to the inclusion of the student, in the sense of frequency and socialization, both in this context and in the other studies observed. The development of new researches that approach the subject is necessary, as well as the continuous discussion in the educational context to provide the effective pedagogical inclusion of deaf students in the context of regular education.